2017
DOI: 10.1590/1678-4499.2016307
|View full text |Cite
|
Sign up to set email alerts
|

Quality peach produced in fertilizer doses of nitrogen and green pruning

Abstract: ABSTRACT:The increasing consumer demand for fruit quality justifies the development of researches that combine orchards management and consumers' perception of the quality of the product. The aim of this study was to evaluate the effect of nitrogen fertilization combined with green pruning intensity on fruit quality of 'Chimarrita' from high density peach trees during three consecutive harvest seasons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
1
11
0
Order By: Relevance
“…Data agree with the ones found by Falguera et al (2012) and Ferreira et al (2016), who did not observe differences in peach color as the result of N fertilization, either. Dolinski et al (2018) observed that peach color was not altered by N fertilization in the first two crops; changes only happened in the third crop, when high chromaticity was found at 214 Kg N ha -1 . Alcobendas et al (2013) state that fruit color is influenced by other factors, such as interaction between irrigation and exposure to sunlight.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Data agree with the ones found by Falguera et al (2012) and Ferreira et al (2016), who did not observe differences in peach color as the result of N fertilization, either. Dolinski et al (2018) observed that peach color was not altered by N fertilization in the first two crops; changes only happened in the third crop, when high chromaticity was found at 214 Kg N ha -1 . Alcobendas et al (2013) state that fruit color is influenced by other factors, such as interaction between irrigation and exposure to sunlight.…”
Section: Resultsmentioning
confidence: 91%
“…Nitrogen (N) is the most important nutrient for stone fruit trees (ROMBOLÀ et al, 2012); it is the second most exported mineral element through fruits yielded by peach trees (TAGLIAVINI et al, 2000) and the most exported one through leaves and twigs (XILOYANNIS;CELANO;NUZZO, 2006). Therefore, N fertilization is essential to peach trees, since it may interfere in aspects related to vegetative growth, productivity and fruit quality (DOLINSKI et al, 2005;FALGUERA et al, 2012;FERREIRA et al, 2018;DOLINSKI et al, 2018). N excess may stimulate vegetative growth of peach trees (DELLA BRUNA;BACK, 2014;FERREIRA et al, 2018), while N deficiency may affect plant photosynthesis (LEAL et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The latter depicts different shades of color with 0 • being absolute red. A negative influence of higher levels of nitrogen on the color formation of fruit skin has previously been reported for 'Gala' and 'Jonagold' apples [17,25] as well as on mango [26], grape [27], and peach [28].…”
Section: Basic Fruit Analysesmentioning
confidence: 81%
“…State standards may lead to N over-fertilization and nitrate leaching in 'Esmeralda' orchards, and it could have potential impact on water quality [28,29]. Excessive vegetative growth has impact on fruit yield and quality [23,25], as well as the incidence of fungal diseases due to decreased air circulation within the canopy [72]. When N addition exceeds its demand by peach trees, vegetative growth is stimulated and it limits sunlight dispersion throughout the canopy [23,35].…”
Section: Foliar Nutrientsmentioning
confidence: 99%
“…Nitrogen (N) shortage decreases flower buds' quality, and it affects the effective fruiting supported by them [19], such a shortage also impairs peach root system growth, affects water and nutrients uptake, and decreases root capacity to sustain shoot growth [20,21] and fruit production [22][23][24]. On the other hand, excessive N doses and high N levels in plant tissue result in vegetative overgrowth, increase in labor costs with green and winter pruning, decrease in fruit quality and increase in disease incidence [23,25,26]. Excessive N applications also lead to N loss due to leaching or runoff, which pose a risk for neighboring water contamination [27][28][29].…”
Section: Introductionmentioning
confidence: 99%